Safety assessment and the effect of squalene isolated from schizochytrium mangrovei pq6 on serum hdl - cholesterol levels in animal models - Ha, Nguyen Cam; Hien, Hoang Thi Minh; Ngan, Nguyen Hoang; Hong, Dang Diem (Academia Journal of Biology, 2019)
In this paper, the acute and subchronic toxicity and the effect of squalene isolated from heterotrophic marine microalga Schizochytrium mangrovei PQ6 on the serum levels of HDL-C were investigated using animal models. The results of acute toxicity study showed that by oral administration of the squalene on albino mice at the highest dose of 58.25 g/kg of whole body of mice/day, the LD50 was not determined. Squalene at doses of 400 mg and 1,200 mg/kg/day for 60 consecutive days have allowed the normal behavior, body weight, hematological and biochemical parameters, liver and kidney functions, morphology of liver, kidney and spleen, total plasma cholesterol content, however, HDL-C level was higher in squalene treated mices compared to control group (p < 0.05). In addition, at doses of 600 and 1,200 mg/kg/day for 60 continuous days, squalene treated mice showed the increase in HDL-C level and HDL-C/total cholesterol ratio and the decrease in the contents of LDL-C and VLDL-C without affecting the body and liver weights and levels of total cholesterol and triglyceride.